STUDENTS' CAPABILITY IN WRITING RECOUNT GENRE OF THE SECOND YEAR STUDENTS OF MTs MUHAMMADIYAH 6 SRIBIT, SRAGEN - SARI , FAIZAH KARTIKA (2010)
This research paper is intended to describe 1) the students' capability in writing recount genre 2) the problems faced by the students in writing recount genre. This study is a qualitative research. In collecting the data, the writer uses observation, interview and document analysis. The technique of analyzing the data involves 1) collecting the data, 2) analyzing the data, 3) getting the percentage, 4) describing the students' capability, 5) describing the problem and problem solving, and 6) drawing conclusion. The result of the study shows that: 1) the students' capability in writing recount text is good, 2) the students have several problems faced in writing recount text, namely: the difficulties in using recount text organization, the difficulties in using correct grammar, the limited vocabulary, the difficulties in arranging the sentences, and the difficulties in looking for the idea